Analisis Pajak Penghasilan (PPh) Pasal 21 Pegawai Tetap Pada PT. Maju Mandiri - Gabriella Christina A.S; Citra Windy Lubis; Emi Masyitah (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2025)
This must be carried out by employers, government treasurers, pension funds, bodies, and activities performed by individuals as domestic taxpayers. This provision is regulated by Law of the Republic of Indonesia Number 36 of 2008 concerning Income Tax, and its derivative regulations, which are continuously updated in accordance with government fiscal policy. This research was conducted by selecting a qualitative approach because it allows for an in-depth understanding of a phenomenon through in-depth analysis of descriptive data, interviews, and observations.